2016
DOI: 10.1080/09506608.2016.1152347
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and fracture of wires and cables for biomedical applications

Abstract: Fine wires and cables play a critical role in the design of medical devices and subsequent treatment of a large array of medical diagnoses. Devices such as guide wires, catheters, pacemakers, stents, staples, functional electrical stimulation systems, eyeglass frames and orthodontic braces can be comprised of wires with diameters ranging from 10s to 100s of micrometres. Reliability is paramount as part of either internal or external treatment modalities. While the incidence of verified fractures in many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 165 publications
1
10
0
Order By: Relevance
“…CoCr alloys also have one order of magnitude greater corrosion resistance in comparison with SSs. Mainly, due to these properties, cobalt and its alloys specially, MP35N, modified 35NLT and Elgiloy, have achieved wide attention for fabrication of K-wires, cerclage wires and guide wires [86].…”
Section: Chemical Composition Alloy Astm Number Applicationmentioning
confidence: 99%
“…CoCr alloys also have one order of magnitude greater corrosion resistance in comparison with SSs. Mainly, due to these properties, cobalt and its alloys specially, MP35N, modified 35NLT and Elgiloy, have achieved wide attention for fabrication of K-wires, cerclage wires and guide wires [86].…”
Section: Chemical Composition Alloy Astm Number Applicationmentioning
confidence: 99%
“…Careful engineering of robust transdermal ports and connectors is usually required to reliably interface external equipment to the implanted device over weeks or months of implantation. Some studies revealed that the bioelectronic system itself does not fail but its interface to the outside does …”
Section: Maturity Of Hybrid Technologiesmentioning
confidence: 99%
“…This may lead to additional residual stresses in the stent, which may affect its deployment once inserted into the body, and may also affect its fatigue endurance when subjected to pulsatile physiological loads. A recent review has also shown significant scatter in the fatigue performance of nitinol wires [ 246 ].…”
Section: Cardiovascular Stents and Their Required Mechanical Propementioning
confidence: 99%